7-Tesla MRI Evaluation of the Knee, 25 Years after Cartilage Repair Surgery: The Influence of Intralesional Osteophytes on Biochemical Quality of Cartilage. (December 2021) - Janssen, M.P.F.; Peters, M.J.M.; Steijvers-Peeters, E.G.M.; Szomolanyi, P.; Jutten, E.M.C.; van Rhijn, L.W.; Peterson, L.; Lindahl, A.; Trattnig, S.; Emans, P.J.
Objective: To evaluate the morphological and biochemical quality of cartilage transplants and surrounding articular cartilage of patients 25 years after perichondrium transplantation (PT) and autologous chondrocyte transplantation (ACT) as measured by ultra-high-field 7-Tesla (7T) magnetic resonance imaging (MRI) and to present these findings next to clinical outcome. Design: Seven PT patients and 5 ACT patients who underwent surgery on the femoral condyle between 1986 and 1996 were included. Patient-reported outcome measures (PROMs) were assessed by the clinical questionnaires: Knee injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC), and Visual Analogue Scale (VAS) for knee pain. The morphological (MOCART score) and biochemical quality (glycosaminoglycans [GAGs] content and collagen integrity) of cartilage transplants and surrounding articular cartilage were analyzed by 7T MRI. The results of the PT and ACT patients were compared. Finally, a detailed morphological analysis of the grafts alone was performed. Results: No statistically significant difference was found for the PROMs and MOCART scores of PT and ACT patients. Evaluation of the graft alone showed poor repair tissue quality and high prevalence of intralesional osteophyte formation in both the PT and ACT patients. Penetration of the graft surface by the intralesional osteophyte was related to biochemically damaged opposing tibial cartilage; GAG content was significantly lower in patients with an osteophyte penetrating the graft surface. Conclusions: Both PT and ACT patients have a high incidence of intralesional osteophyte formation 25 years after surgery. The resulting biochemical damage to the opposing tibial cartilage might be dependent on osteophyte morphology.